Crime on the line. Telemarketing and the changing nature of professional crime - Shover, Neal (The British journal of criminology, 2003)
New opportunities for crimes of acquisition grew significantly in the second half of the twentieth century, but the criminological consequences of this development are poorly charted. We examine offenders who have stepped forward to exploit one category of the new opportunities. Drawing from interviews with 47 criminal telemarketers, we present a picture and interpretation of them, their pursuits and their lifestyles. As vocational predators, they share several important characteristics with the professional thieves sketched by earlier generations of investigators. Like the latter, they pursue a hedonistic lifestyle featuring illicit drugs and conspicuous consumption, and they acquire and employ an ideology of legitimation and defence that insulates them from moral rejection. Unlike professional thieves, however, telemarketing criminals disproportionately are drawn from middleclass, entrepreneurial backgrounds. They are markedly individualistic in their dealings with one another and with law enforcement. Finally, their work organizations are more permanent and conventional in outward appearance than the criminal organizations created by blue-collar offenders, which were grounded in the culture of the industrial proletariat. Our findings show how the backgrounds and pursuits of vocational predators reflect the qualities and challenges of contemporary lucrative criminal opportunities. Like the markets that they seek to manipulate and plunder, the enacted environments of professional criminals embrace infinite variations, and are largely indistinguishable from the arenas that capacitate legitimate entrepreneurial pursuits